2020
DOI: 10.21608/aimj.2020.22069.1054
|View full text |Cite
|
Sign up to set email alerts
|

The association between Helicobacter pylori infection and hyperemesis gravidarum

Abstract: Background: Hyperemesis gravidarum is the severe form of nausea and vomiting of pregnancy. The reported incidence of Hyperemesis gravidarum is about 0.5-2.0%. For the diagnosis of hyperemesis gravidarum there must be presence of three or more vomiting episodes during the day, weight loss of over 5% and ketonuria. Studies have recently suggested that there is an association between emesis gravidarum and hyperemesis gravidarum with Helicobacter pylori infection. Serologically positive H. pylori infection has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…One study (12) agrees with the present study, two groups were created from them: part 1, which consisted of 100 patients with vomiting, and part 2 (controlling group) that included 100 pregnant women without vomiting. In the first part, the authors found the mean of IgG (47.02 ± 36.51) while in the second part the mean (24.97 ± 19.58), and p-value ≤ 0.01.…”
Section: The Mean Level Of Anti-h Pylori Cag a Antibody In Sera Of Pr...supporting
confidence: 52%
See 1 more Smart Citation
“…One study (12) agrees with the present study, two groups were created from them: part 1, which consisted of 100 patients with vomiting, and part 2 (controlling group) that included 100 pregnant women without vomiting. In the first part, the authors found the mean of IgG (47.02 ± 36.51) while in the second part the mean (24.97 ± 19.58), and p-value ≤ 0.01.…”
Section: The Mean Level Of Anti-h Pylori Cag a Antibody In Sera Of Pr...supporting
confidence: 52%
“…It is the most common cause of hospitalization in the first half of pregnancy and second only to preterm labor for pregnancy overall. The etiology of H.G remains unknown, but a number of possible causes have been studied as endocrinal, immunological, psychological, metabolic, genetic, and even infectious such as H.pylori infection (12) .…”
Section: Introductionmentioning
confidence: 99%
“…A number of different diagnostic methods, both invasive and non-invasive are available 14 . The antibody detection is cheap and easy to perform 15 , but may give false positive results. The stool antigen (Ag) test has recently become more acceptable as it is non-invasive, convenient for patients and can be performed easily even in small laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…Hussein (2) documented a significantly higher occurrence of H. pylori in pregnant women who suffer from HG than in women with normal pregnancies (84.4 vs. 42.2%; P = 0.003), which agreed with our results. Also, Elshazly (6) conducted a case-control study which included 200 pregnant women at 6-18 weeks of gestation divided into 2 groups: study group that included 100 pregnant women with emesis gravidarum and control group that included 100 healthy pregnant women and H. pylori IgG testing was done by ELISA. Elshazly (6) found that there was highly significant statistical difference between study group and control group as the mean value of IgG titers in 565 study group was (47.02) but in control group the mean was (24.97) with higher H. pylori seropositivity in pregnant women with emesis gravidarum which agreed with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Elshazly (6) conducted a case-control study which included 200 pregnant women at 6-18 weeks of gestation divided into 2 groups: study group that included 100 pregnant women with emesis gravidarum and control group that included 100 healthy pregnant women and H. pylori IgG testing was done by ELISA. Elshazly (6) found that there was highly significant statistical difference between study group and control group as the mean value of IgG titers in 565 study group was (47.02) but in control group the mean was (24.97) with higher H. pylori seropositivity in pregnant women with emesis gravidarum which agreed with our results. In a systematic review that involved 1,732 participants and controls, Golberg et al (7) observed more cases of HG in pregnant women infected with H. pylori compared to those without H. pylori (pooled OR = 4.45; 95% CI: 2.31-8.54) (2) .…”
Section: Discussionmentioning
confidence: 99%